2019
DOI: 10.1002/phar.2310
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Use and the Risk of Arterial and Venous Thromboembolism in Patients with High‐Grade Gliomas: A Nested Case‐Control Study

Abstract: STUDY OBJECTIVE Bevacizumab is used in the treatment of recurrent glioblastoma, but evidence is limited on the incidence of thromboembolic complications regarding the use of this drug in real-world settings. We evaluated the risk of arterial thromboembolism (ATE) and venous thromboembolism (VTE) associated with the use of bevacizumab among adults diagnosed with high-grade gliomas in a commercially insured U.S. population. DESIGN Nested case-control study. DATA SOURCE Truven Health MarketScan Commercial and Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Similarly, bevacizumab use was not a significant risk factor in either cohort. Previous reports have been conflicting on the thrombogenicity of this drug 40,41 . Despite having been associated with increased VTE risk in hospitalized children previously, 28 OCP use was not a risk factor in our patient population.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, bevacizumab use was not a significant risk factor in either cohort. Previous reports have been conflicting on the thrombogenicity of this drug 40,41 . Despite having been associated with increased VTE risk in hospitalized children previously, 28 OCP use was not a risk factor in our patient population.…”
Section: Discussionmentioning
confidence: 53%
“…Previous reports have been conflicting on the thrombogenicity of this drug. 40,41 Despite having been associated with increased VTE risk in hospitalized children previously, 28 OCP use was not a risk factor in our patient population. This may have been due to the small number of OCP-treated patients in either cohort (Tables 1 and 3).…”
Section: Demographics and Risk Factorsmentioning
confidence: 59%
“…Although the incidence of malignant CNS tumors is higher in men [67], the incidence of VTE and bleeding was similar when considering the subgroup analysis, corroborating previous investigations [31,32,68]. Mulder et al [69] assessed the occurrence of VTE in the first six months of the follow-up and found no difference between the sexes in sub-distribution hazard ratios (SHR = 1.02; 0.98-1.07).…”
Section: Plos Onesupporting
confidence: 73%
“…In studies that provided incidence values by sex (n = 9), 62.7% of participants were men (n = 1,779). Only three studies presented data on patients aged 60 years or older (28,(31)(32), totaling 163 patients with VTE out of 446 patients with CNS (36.5%).…”
Section: Participantsmentioning
confidence: 99%
“…28,[45][46][47][48][49][50][51][52] Another study by Lee et al showed no association between bevacizumab use and thromboembolic events. 53 One study evaluated 4,407 patients via the NSQIP database who underwent resection of a malignant brain tumor between 2007 and 2012. This study included metastatic tumors (n ¼ 1611) and malignant gliomas (n ¼ 2796).…”
Section: High-grade Gliomamentioning
confidence: 99%